Indonesian Policy on Muslim Friendly Tourism: Geopolitical Overview - Yahya, Yuangga Kurnia; Uzair, Achmad; Rofiqo, Azidni (Journal of Critical Realism in Socio-Economics (JOCRISE), 2022)
This article attempts to analyze Indonesia's geopolitical policies in accommodating sharia-based economic and tourism policies. The object of this research is the policy around Muslim-Friendly Tourism (MFT). The tourism sector as one of the largest foreign exchange earners for Indonesia accommodates tourism trends in Muslim-populated countries. This study attempts to analyze the relationship between tourism and Indonesia's international geopolitical policies that involve religious elements, both in macro and micro level. In this study, the researchers found that at the macro level, the government at the national and regional levels provides policies and regulations related to the management and development of MFT. This is driven by phenomena at the micro level related to economic and socio-political aspects. The economic aspect which is dominated by the trend of consumerism of halal products and the socio-political aspect which is dominated by the spirit of Islamic populism in some areas needs to be accommodated by government regulations as a strategy to strengthen the integrity and sovereignty of the nation.